A multimodal electrochemical approach to measure the effect of zinc on vesicular content and exocytosis in a single cell model of ischemia. (3rd November 2021) - Wang, Ying; Gu, Chaoyi; Ewing, Andrew G.
Abstract: Zinc ion is essential for normal brain function that modulates synaptic activity and neuronal plasticity and it is associated with memory formation. Zinc is considered to be a contributing factor to the pathogenesis of ischemia, but the association between zinc and ischemia on vesicular exocytosis is unclear. In this study, we used a combination of chemical analysis methods and a cell model of ischemia/reperfusion to investigate exocytotic release and vesicular content, as well as the effect of zinc alteration on vesicular exocytosis. Oxygen–glucose deprivation and reperfusion (OGDR) was used as an in vitro model of ischemia in a model cell line. Exocytotic release and vesicular storage of catecholamine content were increased following OGDR, resulting in a higher fraction of release during exocytosis. However, zinc eliminated these increases following OGDR and the fraction of release remained unchanged. Understanding the consequences of zinc accumulation on vesicular exocytosis at the early stage of OGDR should aid in the development of therapeutic strategies to reduce ischemic brain injury. As the fraction released has been suggested to be related to presynaptic plasticity, insights are gained towards deciphering ischemia related memory impairment.